ET-Class: An Energy Transfer-Based Classification of Space Debris Removal Methods and Missions - Yalçın, Barış Can; Martinez, Carol; Hubert Delisle, Maxime; Rodriguez, Gonzalo; Zheng, James; Olivares-Mendez, Miguel (Frontiers in Space Technologies, 2022)
Space debris is positioned as a fatal problem for currently operational and future space missions. Many effective space debris removal methods have been proposed in the past decade and several techniques have been either tested on ground or in parabolic flight experiments. Nevertheless, no uncooperative debris has been removed from any orbit until this moment. Therefore, to expand this research field and progress the development of space debris removal technologies, this paper provides review and comparison of the existing technologies with past, present, and future methods and missions. Moreover, since one of the key problems when designing space debris removal solutions is how to transfer the energy between the chaser/de-orbiting kit and target during first interaction, this paper proposes a novel classification approach, named ET-Class (Energy Transfer Class). This classification approach provides an energy-based perspective to the space debris phenomenon, by classifying the way existing methods dissipate or store energy during first interaction.